Coordenação de relés de sobrecorrente e distância para sistemas de transmissão - Marcolino, Matheus Henrique [UNESP] (2014)
The transmission line is a component essential to power systems and your protection its es-sential to ensure a stable and continuous network operation. A appropriate protection system must collect securely and trustily different protection functions. In this work a pilot protectio-nis used, a permissive overreaching transfer trip for extra high voltage lines. This structure uses directional overcurrent relays as backup protections against phase-earth faults and dis-tance relays for phase-phase faults. A intelligent method was developed for mesh networks to coordination relays, as modeling of numerical relay with fuzzy control using MODELS lan-guage to be inserted in ATP (Alternative Transient Program). The proposedmethodology rea-lizes an optimal coordination for all relays in the transmission network. To get this a genetic algorithm is developed. In addition, a fuzzy control is designed in numeric relay, this tool helps the relay on decisions independent of topology changes or different load levels that makes the pilot protection an adaptive protection